Observations of the geomagnetic field by Polar Patrol Balloon (PPB) experiment in Antarctica - Tohyama, Fumio; Fujii, Ryoichi; Ejiri, Masaki; Yajima, Nobuyuki (National Institute of Polar Research, 1993)
P(論文) Two scientific balloon experiments of the Polar Patrol Balloon (PPB) project were performed by the 32nd Japanese Antarctic Research Expedition in December 1990 and in January 1991. Proton precession magnetometers were used to measure the total intensity of the geomagnetic field for studying the underground magnetic structure by detecting magnetic anomalies and geomagnetic variations like pulsations. The first balloon (PPB-1) showed a trajectory through the center of the Magnetic South Pole with a circumpolar trajectory. The total intensity of the geomagnetic field as obtained by the ARGOS data transmission system every 30s with an accuracy of 1 nT during the flight of 22 days. A new proton precession magnetometer system was developed that had a wide dynamical measurement range for the PPB observation. This brief paper reports magnetometry, data processing system and some preliminary results. departmental bulletin paper